'Maggid of Montreal': Rabbi Hirsch Cohen on the dilemmas of the Canadian rabbi - Lapidus, Steven (Canadian Jewish Studies / Études juives canadiennes, 2006)
Tzvi Hirsch Cohen was one of those pioneering eastern European clergy who immigrated to North America in the early twentieth century. So many others stayed put. His goal was to provide a foundation for traditional Judaism in the New World, which he sought to fulfill while serving for decades as Montreal’s first Chief Rabbi. In his speeches, sermons, and writings, Cohen considered how to merge his traditionalist eastern European values and customs with the social mores of democratic and egalitarian Canada. He found particularly vexing the multiple roles rabbis in the New World were called upon to play. In Europe, rabbis were specialized. Some were preachers, others halakhic experts. Cohen viewed the two as being in a state of perennial tension, and he had great difficulty seeing how one rabbi could function as both. Using himself as an example, Cohen’s description of his internal struggles offers a glimpse into the challenges rabbis in the immigrant Orthodox community in early twentieth century Canada had to face.